Blood biomarkers as surrogate endpoints in Alzheimer’s disease research - Shan, Guogen; Li, Hui; Zhang, Yahui; Wang, Guoqiao; Bernick, Charles (Frontiers in Aging Neuroscience, 2025)
BackgroundBlood biomarkers for Alzheimer’s disease (AD) can be utilized as surrogate endpoints to accelerate therapeutic development for this condition.MethodsWe assessed the association between short-term changes in blood biomarkers and long-term declines in cognitive and brain structure volume measures using the ADNI database, with a focus on amyloid-β (Aβ)-positive participants. In our statistical models, the association was calculated after controlling for age, sex, and other possible confounding covariates. Additionally, outliers were removed before running the statistical models to ensure that the results were robust.ResultsA trend association was found between changes in the levels of plasma neurofilament light (NfL) at 12 months and changes in the scores on the Mini-Mental State Examination (MMSE) at 24 months in Aβ-positive mild cognitive impairment (MCI) patients. For Aβ-positive dementia patients, a trend association was observed between changes in plasma p-tau181 levels and changes in whole brain and middle temporal volume.ConclusionIncreased plasma levels of NfL or p-tau181 blood biomarkers were found to be associated with reduced brain volumes and/or declined cognitive outcomes, suggesting that these blood biomarkers may have a predictive role in AD trials.